Diarrheic Syndrome Due to Rotavirus in Immunized and Non-Immunized Children Under 5, in the City of Maracaibo, State of Zulia, Venezuela - R. Atencio; A. Bracho; L. Porto; D. Callejas; L. Costa; F. Monsalve; R. Villalobos; M. Atencio; S. Osorio (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2013)
Acute diarrhea is the most common cause of morbidity and mortality in infants, where rotavirus is one of the main agents involved in severe diarrhea for children under five years. The present study aims to determine the presence of rotavirus in a vaccinated and unvaccinated pediatric population with acute diarrhea that came to the Children's Hospital and the University Hospital of Maracaibo, State of Zulia, for observation from April 2011 to April 2012. One-hundred stool samples were collected and direct agglutination of latex particles was used for diagnosis. 43.6% of the unvaccinated children were positive (24/55) as were 33.3% (10/30) of the vaccinated children. Principally, children under 1 year were affected, predominantly males with 65.9% and females with 40%. Diarrhea due to the viral agent under study accounted for nearly half the hospitalizations for gastroenteritis. A statistically significant difference of p = 0.027 was found between the number of evacuations on the fourth day in unvaccinated (5) and vaccinated (3) children. Results of this research show rotavirus circulating in vaccinated and unvaccinated children. Therefore, the purpose of this report is to alert the medical community to consider that every child with gastroenteritis could possibly have RV.